'Preparing for the next war': the Portuguese army staff corps and the military reforms on the eve of the colonial wars - Rodrigues, L. N. (Bulletin for Spanish and Portuguese Historical Studies, 2012)
This text is part of an ongoing research project on the Portuguese Army Staff Corps, created in the first half of the 19th Century. The project focuses mainly on the period between its modern reorganization, in 1937, and its extinction in 1974. One of the main topics of the project is to evaluate and to understand the way officers from the Portuguese Army Staff Corps (ASF) played a relevant role in preparing the Portuguese Army for the colonial wars that started in Angola in 1961. Since the late 1950s many members of the ASF realized that the next armed conflicts Portugal would have to face would be the wars for national liberation in Africa, therefore, wars of counterinsurgency, very different from the conventional wars they were prepared to fight.